2008
DOI: 10.1080/00387010802428435
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry of Bis-quinolizidine Alkaloids: Differentiation of Stereoisomers and Metamers Using ESI and FAB Mass Spectrometry

Abstract: The ESI and FAB mass spectral fragmentations of seven bisquinolizidine alkaloids were investigated. Fragmentation pathways, elucidation of which was assisted by FAB=CID mass spectra measurements, are discussed. The data create the basis for distinguishing stereoisomers and metamers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…As a continuation of our previous studies of the EI [36][37][38] and fAB 39 mass fragmentations of the derivatives of (-)-sparteine, as well as EI and fAB mass fragmentation of zinc(II) (-)-sparteine and (-)-a-isosparteine complexes, 40 we have extended our investigation to the copper(II) complexes of (-)-sparteine and (-)-a-isosparteine. considerable effort has been devoted to the study of these compounds by infrared and nuclear magnetic resonance spectroscopy, as well as by X-ray methods.…”
mentioning
confidence: 73%
“…As a continuation of our previous studies of the EI [36][37][38] and fAB 39 mass fragmentations of the derivatives of (-)-sparteine, as well as EI and fAB mass fragmentation of zinc(II) (-)-sparteine and (-)-a-isosparteine complexes, 40 we have extended our investigation to the copper(II) complexes of (-)-sparteine and (-)-a-isosparteine. considerable effort has been devoted to the study of these compounds by infrared and nuclear magnetic resonance spectroscopy, as well as by X-ray methods.…”
mentioning
confidence: 73%
“…As a continuation of our previous study [ 15 ] it seems reasonable to extend investigation over FAB mass fragmentation of isomeric oxo-substituted sparteine derivatives. FAB-MS gives useful information for the chemical characterization of different types of alkaloids [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 70%
“…Fast atom bombardment (FAB) mass spectral behaviour of oxo-substituted sparteine derivatives has not been reported in the literature. In a previous work [ 15 ] we described the fragmentation routes of seven bis-quinolizidine alkaloids under fast atom bombardment conditions. We have shown that positional isomers of sparteine derivatives can be differentiated on the basis of their FAB mass spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Defining the fragmentation pathways that small organic molecules (natural products or semi‐synthetic compounds) follow might aid structural characterization. In fact, recent advances in ESI instruments have enabled scientists to assign stereoisomers by ion mobility mass spectrometry and kinetic methods . However, the literature contains just a few examples of how stereochemistry determines the fragmentation pathways that a molecule follows during ESI‐MS/MS analysis .…”
mentioning
confidence: 99%